Narrative Analysis of Maluku Conflict in The Film â€œCahaya dari Timur: Beta Malukuâ€ - Triyono, Agus; Tri L, Nunik Fajar; Satiti, Nur Latifa Umi (Universitas Muhammadiyah Yogyakarta, 2016)
UN (United Nation) notes that 75% of major conflicts in the world are caused by cultural diversity. As multicultural country, Indonesia has high potential for cultural conflict. One of the biggest conflicts that ever occurred in Indonesia is Maluku conflict. This conflict had been retold in the film â€œCahaya dari Timur: Beta Malukuâ€. The research question is â€œHow is the Maluku conflict narrated in the film Cahaya dari Timur: beta Maluku?â€. To answer the question, the researcher chooses the narrative analysis from Tzvetan Todorov.Â He argues that narrative is not flat. It consists of certain levels (equilibrium, disruption, recognizing the disruption, an attempt to the damage, and equilibrium). By dividing film narrative into five levels, this research finds the different condition in equilibrium level. Oftentimes, equilibrium is started by balance condition, but this film is started by conflict. Besides that, Maluku conflict is positioned as the background story.Â